Study of ceramics and porcelain history, and Sio2 and high-K in electrical and electronic application - Lim, Ivy Su Fang (2014)
Outside influences are important inspirations to potters during the period of cultural isolation. As it evolve through the trade of ceramics. Ceramics like textiles are trade across different cultures more easily than paintings as these paintings from unfamiliar cultures cannot be understood. With the advancement of methods applied, ceramics strength and toughness increases over the year.